Uniform loading on the reinforced concrete beam produced by the specific cylinder-shaped rubber bags fully filled with air or water. Issue 9 (July 2020) - Chen, Dapeng; Chen, Li; Fang, Qin; Zheng, Yuzhou; Pan, Teng
The bending behavior of reinforced concrete beams under uniform pressure is critical for the research of the blast-resistance performance of structural components under explosive loads. In this study, a bending test of five reinforced concrete beams with the dimensions of 200 mm (width) × 200 mm (depth) × 2500 mm (length) under uniform load produced by a specific cylinder-shaped rubber bag filled with air or water was conducted to investigate their flexural performances. An air bag load was applied to three of the reinforced concrete beams, a water bag load was applied to one reinforced concrete beam, and the remainder beam was subjected to the 4-point bending load. The experimental results highlighted that the air bag and water bag loading methods can be used to effectively apply uniform loads to reinforced concrete beams. Moreover, the stiffness of the air bag was improved by 123% in accordance with the initial pressure increases from 0.15 to 0.45 MPa. In addition, a finite element model of the test loading system was established using ABAQUS/Standard software. Moreover, the critical factors of the air bag loading method were analyzed using the numerical model. The calculated results were found to be in good agreement with the test data. The established finite element model can therefore be used to accurately simulate the action performances of the uniform loading technique using rubber bags filled with air or water.